(untitled) (Research, Society and Development, 2022)
How Integrative and Complementary Practices take into account the integrality of the individual and thus seek health treatment through natural health means. Such were inserted in the middle of the National Health Policy (SUS) through the Single Health Ordinance (SUS) through the Integrative Health Care Ordinance, with emphasis on humanized care, welcoming listening and integration with the environment and the community. This study aimed to describe the implementation process of the first outpatient clinic of the university PICS in Belém/PA. This is a descriptive study, with a qualitative approach, of the experience report type, carried out from February to June 2022, at the Clinical Pharmacy Clinic (FARMCLIN). Meetings were held to decide on the inclusion of practices to be offered in the outpatient clinic of the UBS implementation unit, with the professional as the protagonist in the inclusion of the UBS’s integrated practices. The analyzes carried out were carried out during the protection and attention given in the attention to the environment of the PICS to the contribution in the promotion, recovery of the patient’s health.